Hubungan Motivasi Belajar dengan Disiplin Belajar pada Mata Kuliah Pemangkasan Rambut Mahasiswa Program Studi D4 Tata Rias dan Kecantikan - Mardiyah, Laila; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This article aims to reveal the relationship between motivation to learn the Discipline Learning course on hairdressing student of Jurusan Tata Rias dan Kecantikan Fakultas Pariwisata dan Perhotelan UNP.This research is a quantitative descriptive correlational. The population in this study were all students of batch 2013 Department of Jurusan Pendidikan Tata Rias dan Kecantikan, the sampling technique is total sampling. Data collection techniques is using a questionnaire (questionnaire) by using Likert scale. Mechanical analysis of the level of achievement of respondents with a percentage formula, test requirements analysis using normality test and linearity test, while using the Pearson correlation coefficient analysis Product Moment Correlation and continued with the t test for significance analysis of the correlation coefficient and hypothesis testing.Based on the analysis of data obtained an average score of 58.67% percentage of learning motivation with low category, Discipline Learning is the percentage of 54.75% with a low category. The results of the analysis of correlation of 0.615 with the interpretation of a strong correlation, while the test based on the mean of the correlation obtained by the price t count> t table (3,613> 2.011) which means that Ha which reads